Use of Blockchain Technology and AI in Sharia Financial Risk Management - Hendarti, Yanita; Winarno, Budi; Primbang Aprilianto, Muhammad (Ann Publisher, 2024)
In an era of increasing globalization and business complexity, the management of Islamic financial risk has become a primary concern for Islamic financial institutions. This research aims to investigate the potential use of blockchain technology and artificial intelligence (AI) in enhancing the effectiveness of Islamic financial risk management. Through a literature review method, this study details recent advances in the utilization of blockchain technology for transparency and security of Islamic financial data, as well as the implementation of AI for predictive analysis and fraud detection. The results indicate that blockchain integration can reduce the risk of data manipulation, while AI provides the capability to identify potential risks more quickly and accurately. However, challenges such as legal aspects, regulations, and technology adaptation need to be considered. In the context of Islamic finance, this research provides insights into how blockchain technology and AI can transform the paradigm of financial risk management, creating opportunities for increased efficiency and sustainability within the Islamic financial system. The practical implications of these findings underscore the importance of strategic planning in adopting these technologies to ensure compliance with Sharia principles and maximize their benefits.